The socio-economic impacts of refurbished computers on small and medium enterpirses (SME) in Mombasa Kenya, and the role of the formal sector in promoting circular economy - Sugow, Yussuf (2022)
The dependence and use of information and communication technology (ICT) tools remain part of modern society’s daily life. The increased use of electronic devices such as computers and mobile phones have significantly impacted global e-waste generation in recent years. However, effective e-waste management could be a strategy to divert e-waste streams into socio-economic potentials to protect the environment and improve society’s wellbeing. In the global north, effective e-waste policy, such as the EU directive, and active extended producer responsibility (EPR) help in tackling e-waste streams, while lack of e-waste policy and frameworks in the global south catalyse the generation of e-waste streams. However, social enterprises help societies in the global south deal with the mess of e-waste challenges and convert it to economic potentials. One of the social enterprises working to improve e-waste management in Kenya is Close the Gap (CTG), which plays a crucial role in effective e-waste management by providing training to small and medium businesses (SMEs), creates awareness, and prolong devices’ lifetime by refurbishing them. The company recently established a circular economy hub (CE-Hub) to accelerate the promotion of a circular economy (CE) business models. To understand the potential impacts of e-waste, this thesis investigates the socio-economic impacts of refurbished computers on SMEs and how the CTG promotes effective e-waste management in transitioning to CE business models in Mombasa, Kenya. The study applied qualitative interviews to understand interviewees' life experiences on e-waste management and how the operation of the CE-Hub impacts their social and economic wellbeing. The study results showed that the operation of CTG together with her new CE-Hub facility brought employment opportunities for unemployed youth, promote effective e-waste management, and improved livelihoods. The findings clearly indicate that providing support, training, and awareness creation on e-waste management to SMEs and local community could accelerate the CE transition in Kenya.